Analysis of Retinal Perfusion in Children, Adolescents, and Young Adults with Type 1 Diabetes Using Optical Coherence Tomography Angiography. (8th May 2019) - Mameli, Chiara; Invernizzi, Alessandro; Bolchini, Alice; Bedogni, Giorgio; Giani, Elisa; Macedoni, Maddalena; Zuccotti, Gianvincenzo; Preziosa, Chiara; Pellegrini, Marco
Abstract : We performed a cross-sectional study to analyze the retinal vasculature in children, adolescent, and young adults with type 1 diabetes using optical coherence tomography angiography (OCTA). Patients underwent funduscopic examination for diabetic retinopathy (DR) screening during an annual visit for the screening of diabetes-related complications which included the evaluation of glycated hemoglobin (HbA1c), microalbuminuria, lipid profile, arterial pressure, and neurological assessment. In addition, OCTA of the retinal vasculature was performed. Quantitative analysis of the OCTA images evaluated the vessel density at the superficial (SCP) and deep (DCP) capillary plexus of the retina. Structural vascular alterations were evaluated qualitatively. Results were compared to those obtained in a group of healthy age-, sex-, and pubertal stage-matched controls. The effect of age, disease duration, age at the disease onset, mean HbA1c since the onset, and lipid profile on vascular density was tested. Fifty-three patients (median age 15.5, IQR 12.4-19.4 years; 57% females) with type 1 diabetes and 48 controls were enrolled. The median (IQR) HbA1c was 7.6% (60 mmol/mol) (6.9-8.1%, 52-65 mmol/mol), and the median (IQR) duration of disease was 6.0 (3.3-10.3) years. Mean vessel density measured with OCTA was lower in patients compared to controls with the temporal sector showing the highest difference both in the SCP (0.55 vs. 0.57, p < 0.001 ) and the DCP (0.63 vs. 0.65, p < 0.001 ). None of the predictors was associated with the superficial and deep vascular densities. Only 2 patients had clinically detectable DR. Microvascular structural changes were found on OCTA in both of these patients and in one without funduscopic alterations. In conclusion, patients with type 1 diabetes without clinically detectable DR had decreased capillary density compared to controls on OCTA images. These findings may provide useful information for the screening and the management of patients with type 1 diabetes. Further studies are needed to confirm our results and their clinical relevance.